The evolution of business ethics research in the realm of tourism and hospitality: A bibliometric analysis. Issue 8 (8th August 2016) - Köseoglu, Mehmet Ali; Sehitoglu, Yasin; Ross, Gary; Parnell, John A.
Abstract : Purpose: This paper aims to illustrate how business ethics research is progressing in the tourism and hospitality (T/H) industries and suggest a research agenda. Design/methodology/approach: This study applies bibliometric analysis to articles related to business ethics topics in the T/H fields published between 1995 and 2014 in six, nine and five leading hospitality-, tourism- and business ethics-oriented journals, respectively. Findings: This study provides a broad view on business ethics research in the T/H fields based on leading authors, institutions, themes and methods used over the past two decades. Research limitations/implications: This study assesses the progress of business ethics research in the hospitality and tourism fields. Only articles published in select, prominent Social Sciences Citation Index journals were analyzed. Practical implications: This analysis focuses on published articles related to business ethics in the T/H fields. As such, it facilitates researchers, academic scholars and professionals in contributing to the field more effectively and advancing scientific progress in the literature. It aids practitioners by evaluating the extent to which scholars have investigated key issues in the field. Originality/value: This study is the first to utilize bibliometric analysis to assess business ethics research focusing on T/H activities published in leading tourism, hospitality and business ethics journals.